Exploring the Treatment Methods of Urolithiasis - Fedorowicz, Sebastian; Suława, Adrian; Targoński, Oskar; Targońska, Marta; Furgalska, Julia; Basiak, Aneta; Buczek, Agnieszka; Ptasiński, Aleksander; Niekurzak, Rafał (Quality in Sport, 2024)
Introduction: Urolithiasis, characterized by the formation and deposition of crystal agglomerates within the urinary tract, is a prevalent condition affecting up to 20% of the global population. This disease is considered systemic, as its rising incidence is linked with comorbidities such as obesity, diabetes, hypertension, and chronic kidney disease. The growth of kidney stones can obstruct urine flow in the kidney, ureter, bladder, or urethra, potentially causing acute symptoms such as renal colic, which manifests as sharp pain in the lower back or abdomen radiating to the groin, accompanied by nausea, vomiting, hematuria, or dysuria. State of knowledge: Conservative treatment methods for urolithiasis include the administration of non-steroidal anti-inflammatory drugs (NSAIDs) and paracetamol, along with adequate hydration. However, surgical intervention may be necessary in certain cases. Current surgical treatments encompass minimally invasive techniques such as extracorporeal shock wave lithotripsy (ESWL), ureteroscopy (URS), retrograde intrarenal surgery (RIRS), and percutaneous nephrolithotomy (PCNL), as well as traditional open surgical procedures including nephrolithotomy, cystolithotomy, pyelolithotomy, and ureterolithotomy. Additionally, there are modified and combined approaches such as endoscopic combined intrarenal surgery (ECIRS), mini-PCNL, and ultra-mini PCNL. The aim of this article: This article aims to demonstrate the epidemiology and risk factors associated with kidney stone formation and to provide a comprehensive review of the surgical treatment options for urolithiasis. Conclusion: The treatment method for urolithiasis should be chosen individually for each patient, taking into account the patient’s specific anatomy and characteristics, stone localization and size, past history and the whole clinical picture.